Psychosocial self-efficacy in young people with diabetes mellitus and its influence on self-care - Evelin Matilde Arcain Nass; Sonia Silva Marcon; Elen Ferraz Teston; Maria do Carmo Fernandez Lourenço Haddad; Pamela dos Reis; Iven Giovanna Trindade Lino (Universidade Federal do Ceará, 2019)
Objective: to identify psychosocial self-efficacy in young people with Type 1 diabetes mellitus and its association with sociodemographic variables, health profile, and search for health care. Methods: cross-sectional study conducted with 35 young people through audio-recorded interviews. Two instruments were used: a) script for characterization of sociodemographic data, health profile, and search for health care; b) Diabetes Management Self-Efficacy Scale - Short Version. In the analysis, we used descriptive and inferential statistics - Chi-square test and Fisher's Exact test. Results: all young people had satisfactory (moderate and high) self-efficacy levels. Although not statistically significant, there was a slightly higher proportion of high self-efficacy in young males, people over 18 years old, white skinned, unemployed, with overweight, with health insurance, with more than eight years of diagnosis, and not hospitalized. Conclusion: young people present satisfactory self-efficacy, without significant association with sociodemographic and clinical variables.